The effectiveness of extension work in educational institutions in Algeria A field study on a sample of school and vocational guidance and counseling counselors in the state of Mughayir - BENTAHAR, Imad; ALICHERIF, Houria (Social Sciences Journal, 2021)
The current study aims to identify the effectiveness of counseling work in educational institutions in Algeria from the point of view of a sample of school and vocational guidance and counseling counselors in the state of Al-Mughir, as well as to identify the degree of effectiveness of media classes and counseling interviews in counseling work. To collect information, a questionnaire was used to measure the level of counseling work that includes fourteen paragraphs (14) applied to a sample of twenty (20) counselors for school and vocational guidance and counselling, and after using the SPSS version 22 programs in analyzing the results of the study, it was concluded that the degree of The effectiveness of counseling work in educational institutions is great, and media sessions and counseling interviews contribute greatly to the effectiveness of counseling work, and some recommendations were made to activate counseling work in educational institutions to contribute more to improving the educational level.